Ultrastructural study of closed macular hole- preliminary application of a novel high magnification module combining with OCT - Chang-Yu Qiu; Yuan-Yuan Shi; Hong-Wei Zhao; Chuang Nie; Ming-Xia Dong; Huai-Qiang Zhang; Jun Zhao; Qian-Qian Xu; Fei-Long Song; Xiao-Hua Guo; Lin Shi; Chang-Ying Liu; et al. (BMC Ophthalmology, 2021)
Abstract Background As a novel high magnification module (HMM) combining with OCT (OCT-HMM) is able to detect the microstructure of retina, we apply it to explore the ultrastructure of the macula after closure of the idiopathic macular hole (IMH) by surgery. Methods This is an observational case series study in which patients with full-thickness IMHs who had undergone successful macular closure by vitrectomy and internal limiting membrane peeling and healthy subjects were recruited. After comprehensive ophthalmic examinations, the images of macular area were obtained and collected by professional operators using OCT-HMM. Then images were independently analyzed by 4 masked vitreoretinal specialists. Results A total of 24 IMH eyes and 42 healthy eyes were examined. HMM images were obtained in 10 IMH eyes. Among them, 4 eyes whose macula closed completely with recovery of photoreceptor layer presented a dark arc nasal to the fovea, oriented to the optic, and the notch of arc faced temporally. Six eyes in which the macula closed incompletely with photoreceptor cells loss revealed a dark ring with uneven bright spots inside. The other 14 eyes failed to obtain clear images by OCT-HMM. The contra lateral eyes of the patients and the healthy subjects’ eyes succeeded to obtain the HMM images which displayed evenly grey background thickly covered with tiny bright dots that was in similar size and evenly and widely distributed and there no dark arc or ring. OCT B-scan and IR images could be acquired in all of the IMH and healthy eyes. Conclusion The preliminary application of HMM has supplied us a brand-new insight into the microstructure of closed IMH. A dark arc sign could be detected with OCT-HMM in the macula which was functionally closed after surgery that was probably the healing mark on a microstructure photoreceptors level. Its existence and shape indicated that the functional closure followed by a retinal displacement mainly horizontally from temporal side to nasal side but not symmetric centripetally.